The role of consumer fanaticism in the acceptance of brand extensions: merchandising in the video games market - Young, Joshua; Marchegiani, Chris (School of Marketing, Curtin Business School, 2010)
In the modern marketing environment, many brands seek to expand into new markets while taking advantage of their existing brand name and resources to ensure the success of the venture. However like the introduction of any new product, success is not guaranteed and many factors must be considered when planning the introduction of a brand extension. Aaker and Keller (1990) explain that the "perceptual fit (i.e., whether a "consumer perceives the new item to be consistent with the parent brand") is a key element in predicting brand extension success" for a number of reasons including "that the transfer of perceived quality of a brand will be enhanced when the two product classes in some way fit together" (Aaker and Keller. 1990, 29). One group of consumers which would be thought to respond more positively towards brand extensions is fanatics as this type of consumer have a wish to acquire products related to their area of fanaticism and often exhibit extraordinary devotion towards a brand or product of which they are a fan. (Thorne and Bruner 2006) The video games industry is a market which has over the years grown to be one of the main sources of entertainment products in the modern marketplace and is only now reaching maturity. This is a market in which consumer fanaticism is prevalent and in which merchandise is regularly produced to tie in with existing video games/game franchises (i.e. brand extensions). This study explores the effect which fanaticism has on the acceptance of brand extensions with differing levels of parent brand congruency by video game fans. Respondents were asked to specify their favourite game from the last five years and to apply questions relating to fanaticism and hypothetical brand extensions to that particular game. Three products were chosen as brand extensions in; a video game controller/gamer keyboard, a beanbag and a pair of shoes. These were intended to represent products of high, medium and low parent brand congruency, respectively. However final results indicated that there was not a significant difference between respondents' ratings of the beanbag and the shoes and so both were used to represent low congruency products. Respondents were split into two groups; group1 being 'low fans' exhibiting a relatively low level of fanaticism towards video games and group2 being 'high fans' exhibiting a relatively high level of fanaticism towards video games. The ratings given by these two groups in relation to the three products were then compared and it was found that, the high fans gave consistently higher ratings to all three products in terms of congruency and purchase intention than the low fans. In many cases the high fans ratings were significantly higher than that of the low fans. The ratings were then compared between the products with the most interesting finding relating to the differences in respondents' ratings of purchase intention. It was found that while in relation to parent brand congruency; the high fans almost always gave significantly lower ratings to the low congruency products than the low fans gave to the high congruency product, there was no significant difference between the purchase intention ratings given by the high fans to the low congruency products and those given by the low fans to the high congruency product. This result suggests that while congruency was a consideration in this case, the level of fanaticism exhibited by a particular target market must also be examined when planning the introduction of a new brand extension.